Between Mahar and Uang Panai: A Comparative Study of Islamic Family Law and Customary Law in Marriage Traditions of South Sulawesi - Nurhikmah, Nurhikmah; Purnamasari, Nur Indah; Nursalam, Nursalam (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to examine the differences in the concept and practice of mahr in Islamic family law and uang panai in the customary law of South Sulawesi, as well as their implications for marriage traditions in the region. The research employs a qualitative method with a comparative study approach, involving the collection of primary data through in-depth interviews with religious leaders, customary leaders, and local community members, alongside a literature review related to Islamic law and customary law. The findings indicate that mahr in Islam is a flexible and non-burdensome obligation, serving as a symbol of respect and commitment from the husband to the wife, in accordance with principles of justice and consent. Conversely, uang panai in South Sulawesi customary law carries a higher value and functions as a symbol of dignity and respect towards the bride’s family, with amounts often constituting a heavy burden on the groom’s side. This study highlights a common misunderstanding within the community that equates mahr with uang panai, resulting in social and economic pressures. The study recommends the need for education and adaptation of traditions so that marriages can proceed in accordance with Islamic principles without neglecting local cultural values proportionally and fairly. Abstract: Penelitian ini bertujuan untuk mengkaji perbedaan konsep dan praktik mahar dalam hukum keluarga Islam dengan uang panai dalam adat Sulawesi Selatan, serta implikasinya terhadap tradisi pernikahan di wilayah tersebut. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi komparatif, teknik pengumpulan data primer berupa wawancara mendalam dengan tokoh agama, tokoh adat, dan masyarakat setempat, serta studi literatur terkait hukum Islam dan adat. Hasil penelitian menunjukkan bahwa mahar dalam Islam merupakan kewajiban yang fleksibel dan tidak memberatkan, berfungsi sebagai simbol penghormatan dan komitmen suami kepada istri, sesuai dengan prinsip keadilan dan kerelaan. Sebaliknya, uang panai dalam adat Sulawesi Selatan memiliki nilai yang lebih tinggi dan berfungsi sebagai simbol harga diri serta penghormatan terhadap keluarga perempuan, dengan nilai yang sering kali menjadi beban berat bagi pihak laki-laki. Studi ini menyoroti adanya ketidaksepahaman di masyarakat yang sering menyamakan mahar dengan uang panai, sehingga menimbulkan tekanan sosial dan ekonomi. Penelitian ini merekomendasikan perlunya edukasi dan penyesuaian tradisi agar pernikahan dapat berjalan sesuai dengan prinsip Islam tanpa mengabaikan nilai budaya lokal secara proporsional dan adil.